2021
DOI: 10.1001/jamanetworkopen.2021.28991
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Discordance Between Physicians and Family Members Regarding Prognosis in Patients With Severe Acute Brain Injury

Abstract: IMPORTANCE Shared decision-making requires key stakeholders to align in perceptions of prognosis and likely treatment outcomes. OBJECTIVE For patients with severe acute brain injury, the objective of this study was to better understand prognosis discordance between physicians and families by determining prevalence and associated factors. DESIGN, SETTING, AND PARTICIPANTSThis mixed-methods cross-sectional study analyzed a cohort collected from January 4, 2018, to July 22, 2020. This study was conducted in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…As clinician’s lead conversations about best medical options and prognosis, the family is invited to share the patient’s narrative and preferences. Since the disagreement between clinicians and families is widened by mutual misunderstanding of prognostic assessment [ 44 ], validated scores could be helpful in reducing this gap and facilitating these conversations. More specifically, training programs focused on prognostic assessment and predictive scores could facilitate their application in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…As clinician’s lead conversations about best medical options and prognosis, the family is invited to share the patient’s narrative and preferences. Since the disagreement between clinicians and families is widened by mutual misunderstanding of prognostic assessment [ 44 ], validated scores could be helpful in reducing this gap and facilitating these conversations. More specifically, training programs focused on prognostic assessment and predictive scores could facilitate their application in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians must balance a range of ethically challenging and complex demands, including providing treatment consistent with the patient’s presumed preferences and values; supporting the patient’s family and loved ones; ensuring timely decision-making and overseeing clinical care 1. However, as the literature has shown, there is often a considerable gap between the care that is received and the care patients would have wanted 2 3. Moreover, available instruments to record goal of care preferences, such as advance directives, still do not provide the guidance clinicians often need to identify patient preferences 4 5.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, as the literature has shown, there is often a considerable gap between the care that is received and the care patients would have wanted. 2 3 Moreover, available instruments to record goal of care preferences, such as advance directives, still do not provide the guidance clinicians often need to identify patient preferences. 4 5 Moreover, those close to the patient tend to be part of the decision-making process, but research has shown that surrogates and next-of-kin are often limited in their ability to accurately predict their loved ones’ preferred care 6 7 and often suffer emotional distress in the face of such decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…13 Data from the adult neurocritical care setting suggests that prognostic discordance between physicians and surrogates is common in the context of differences in understanding and optimistic beliefs. 14 Existing data in the adult traumatic brain injury setting further suggest that adult surrogates and clinicians have different prognostic communication preferences from each other. Whereas adult surrogates value the provision of numeric prognostic estimates and the reduction of prognostic uncertainty, clinicians often prefer to omit numeric estimates in the context of perceptions of surrogate numeracy and insufficient data to support prognostication.…”
mentioning
confidence: 99%
“…Adult surrogate decision‐makers highly value information about death and neurologic outcome, even in the face of uncertainty 13 . Data from the adult neurocritical care setting suggests that prognostic discordance between physicians and surrogates is common in the context of differences in understanding and optimistic beliefs 14 . Existing data in the adult traumatic brain injury setting further suggest that adult surrogates and clinicians have different prognostic communication preferences from each other.…”
mentioning
confidence: 99%